1987
DOI: 10.1042/bj2460547
|View full text |Cite
|
Sign up to set email alerts
|

Cystine exodus from normal leucocytes is stimulated by MgATP

Abstract: Cystine exodus from partially purified granular fractions of normal leucocytes is stimulated by MgATP. N-Ethylmaleimide, an inhibitor of the lysosomal H+-translocating ATPase, eliminated the stimulated exodus, but had no effect on basal exodus. As the initial content of cystine was increased, the initial velocity of both the basal and ATP-stimulated egress increased. However, as saturation with substrate was approached, the ATP stimulation disappeared leaving only the N-ethylmaleimide-insensitive basal exodus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Another study reported that in lysosomes from human leukocytes, cystine efflux was not stimulated by the H + ‐ATPase (Gahl and Tietze, 1985). However, an excessive lysosomal loading of cystine (artificially performed using a methyl ester derivative) might have masked the transporter‐mediated process in these experiments (Greene et al ., 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that in lysosomes from human leukocytes, cystine efflux was not stimulated by the H + ‐ATPase (Gahl and Tietze, 1985). However, an excessive lysosomal loading of cystine (artificially performed using a methyl ester derivative) might have masked the transporter‐mediated process in these experiments (Greene et al ., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, previous studies on leukocytes (Gahl et al ., 1982a; Greene et al ., 1987), lymphoblasts (Jonas et al ., 1982b, 1983), fibroblasts (Smith et al ., 1987) and rat liver (Jonas, 1986) have shown that cystine efflux from lysosomes is stimulated by Mg‐ATP. The use of inhibitors and uncouplers showed that the effect of ATP is mediated by the lysosomal H + ‐ATPase (Jonas et al ., 1983; Jonas, 1986; Smith et al ., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when the transmembrane pH gradient between the acid extracellular medium and the neutral cytosol is disrupted, cystine transport is abolished (Fig. Most of the studies of cystine transport on whole lysosomes isolated from leukocytes [9,38], lymphoblasts [39,40], and fibroblasts [41] suggested that cystine efflux was stimulated by Mg-ATP. Thus the H + -translocating ATPase that acidifies and positively charges the lysosomal lumen actively drives the cystinosin-mediated transport in the efflux direction (Fig.…”
Section: Function Of Cystinosinmentioning
confidence: 99%
“…Since this discovery, many other characteristics of the lysosomal cystine transport system have been elucidated in a variety of cell types including human leucocytes, human lymphoblasts, human fibroblasts, mouse fibroblasts, rat liver cells and FRTL-5 cells [1,2,20,21,[25][26][27][28][29][30][31][32][33]. This transport route recognizes the L-isomer of cystine and selenocystine with the highest affinity and weakly recognizes cystathionine, cysteamine-cysteine mixed disulfide and cystamine as indicated by their ability to moderately inhibit lysosomal cystine transport [21,25].…”
Section: L-fucosementioning
confidence: 99%
“…Efflux of cystine from lysosomes occurs with a halftime of 25-45 min at 37 °C and pH 7.0 in human leucocytes, fibroblasts and lymphoblasts and is stimulated 2-3-fold by MgATP [1,2,[27][28][29][30][31][32]. Several studies have shown that this stimulatory effect of MgATP on lysosomal cystine exodus correlates with an increase in the transmembrane proton gradient and/or a decrease in the potential across the lysosomal membrane [28,29,32].…”
Section: L-fucosementioning
confidence: 99%